The Importance of Corporate Culture for the Sustainability of Companies in the Context of Crisis Phenomena - M. A. Izmailova (Модернизация, инновация, развитие, 2022)
Purpose: the purpose of the article is to study the role of corporate culture in the sustainability of companies in the conditions of crisis phenomena, as well as to analyze methodological approaches to corporate culture as a tool for the competitive success of the company.Methods: the methodology of the work is based on the use of the concepts of organizational culture and sustainable development, as well as the theory of modernization, integrating economic growth and the culture of companies within a single process of sustainable development. A group of scientific methods has been applied, including: inductive-deductive method, method of comparative analysis and retrospective method, method of expert analysis, rating assessment and others.Results: the analysis of the role of corporate culture in the conditions of crisis phenomena caused by the instability of the external environment is carried out. It is noted that the influence of corporate culture on the stable development of companies can have a dual character: a strong corporate culture has a stimulating effect on the economic growth of the company, and its weakness becomes an obstacle to sustainable development. The analysis of methodological approaches to corporate culture, which is considered as a tool for competitive success and sustainable development of the company, is carried out. Modern aspects of the formation of new behavioral models and tools for their introduction into corporate culture are revealed in order to maximize the compliance of companies with the conditions of extreme instability of the external environment.Conclusions and Relevance: the phenomenon of corporate culture is a rather complex area of research – this follows from the interpretation of this concept, the definition of the methodology of formation and the search for tools for its development. But it becomes obvious that the growth of knowledge about corporate culture, produced in the academic environment and highly demanded by the management of companies, has had a significant impact on managerial thinking and management practice. This is due to the understanding of the high role of corporate culture in the processes of internal integration and adaptation of the company to the external environment, in achieving competitive success and strategic development goals, which creates the basis for sustainable development of the economic system.